STUDI SOSIAL EKONOMI MASYARAKAT TERTINGGAL DI KENAGARIAN GARABAK DATA KECAMATAN TIGO LURAH KABUPATEN SOLOK - Sari, Beni - (Pendidikan Geografi, 2014)
This study aims to determine Socioeconomic Disadvantaged Communities in the District Data Garabak Kenagarian Tigo seen Solok district headman of: 1) education, 2) the level of income, 3) the type of livelihood and 3) the interaction between people.This research is descriptive. The population in this study is the head of the family who live in Garabak Data Village Tigo Lurah District of Solok Regiontotaling 665 households. Samples were taken with a proportional random sampling technique with a proportion of 10% that the sample amounted to 56 families.The results of the study found that: 1) The level of education communities in Garabak Data Village Tigo Lurah District of Solok Region generally complete primary school (33,93%), (2) The level of income of the people in Garabak Data Village Tigo Lurah District of Solok Region general Rp. 500000- Rp 1.000.000 (57,14%), (3) The livelihood of the people in Garabak Data Village Tigo Lurah District of Solok Region quite varied that much that farming is at least 60.71% which is 1.79% of civil servants and (4) Interaction between communities in Garabak Data Village Tigo Lurah District of Solok Region public relations in the left and right, good 71.43% and excellent 28.57%.